User Acceptance Of Internet Banking In Penang - OH, SOOK MAY (2005)
Internet banking has pervaded our lives and threatened the very existence of the traditional financial institution. There is a big business prospect for financial institutions to consider making Internet banking as a new delivery channel and to study the acceptance of customers to Internet banking. This study investigates the dominant factor(s) that influence the user intention to use Internet banking in Penang. Three popular models; Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB) and Technology Acceptance Model are examined and compared.